UGA is read as tryptophan in Mycoplasma capricolum. - Yamao, F (1985)
UGA is a nonsense or termination (opal) codon throughout prokaryotes and eukaryotes. However, mitochondria use not only UGG but also UGA as a tryptophan codon. Here, we show that UGA also codes for tryptophan in Mycoplasma capricolum, a wall-less bacterium having a genome only 20-25% the size of the Escherichia coli genome. This conclusion is based on the following evidence. First, the nucleotide sequence of the S3 and L16 ribosomal protein genes from M. capricolum includes UGA codons in the reading frames; they appear at positions corresponding to tryptophan in E. coli S3 and L16. Second, a tRNATrp gene and its product tRNA found in M. capricolum have the anticodon sequence 5' U-C-A 3', which can form a complementary base-pairing interaction with UGA.